Targeted Inhibition of Fibroblast Growth Factor Receptor 1-GLI Through AZD4547 and GANT61 Modulates Breast Cancer Progression - Riaz, Syeda Kiran; Khan, Walizeb; Wang, Fen; Khaliq, Tanwir; Malik, Amber; Razia, Eisha Tir; Khan, Jahangir Sarwar; Haque, Shafiul; Hashem, Anwar M.; Alkhayyat, Shadi S.; Azhar, Najiah Esam; Harakeh, Steve; et al. (Frontiers in Cell and Developmental Biology, 2021)
The underlying mechanism of FGFR1 mediated carcinogenesis is still not fully understood. For instance, FGFR1 upregulation leads to endocrine therapy resistance in breast cancer patients. The current study aimed to identify FGFR1 linked genes for devising improved therapeutic strategies. RNA-Seq and microarray expression data of 1425 breast cancer patients from two independent cohorts were downloaded for the analysis. Gene Set Enrichment Analysis (GSEA) was performed to identify differentially expressed pathways associated with FGFR1 expression. Validation was done using 150 fresh tumor biopsy samples of breast cancer patients. The clinical relevance of mRNA and protein expression of FGFR1 and its associated genes were also evaluated in mouse embryonic fibroblast (MEFs) and breast cancer cell line (MDA-MB-231). Furthermore, MDA-MB-231 cell line was treated with AZD4547 and GANT61 to identify the probable role of FGFR1 and its associated genes on cells motility and invasion. According to GSEA results, SHH pathway genes were significantly upregulated in FGFR1 patients in both discovery cohorts of breast cancer. Statistical analyses using both discovery cohorts and 150 fresh biopsy samples revealed strong association of FGFR1 and GLI1 a member of SHH pathway. The increase in the expression of these molecules was associated with poor prognosis, lymph node involvement, late stage, and metastasis. Combined exposures to AZD4547 (FGFR1 inhibitor) and GANT61 (GLI1 inhibitor) significantly reduced cell proliferation, cell motility and invasion, suggesting molecular crosstalk in breast cancer progression and metastasis. A strong positive feedback mechanism between FGFR1-GLI1 axis was observed which significantly increased cell proliferation and metastasis. Targeting FGFR1-GLI1 simultaneously, will significantly improve the prognosis of breast cancer in patients.